Evaluación del proceso de formalización minera del pequeño productor minero y pequeño minero artesanal del departamento de Madre de Dios en base al cumplimiento del Decreto Legislativo N°1336 - Revilla Paz, Andrea Gladys (2024)
The current study focuses on evaluating the mining formalization process of the PPM and PMA of Madre De Dios based on compliance with D.L No. 1336 in the period 2017-2022. Based on this, it is possible to know the progress of the formalization of small-scale miners on the established work dates. For the research, a descriptive-non-experimental design was used, with a population of 9,251 informal miners, who are registered in the REINFO of the region. Also, the data collection technique was used through the analysis and review of documents from the DREMEH of Madre de Dios and the MINEM, as well as books, research, standards, and studies found on the Internet. As a result, it was obtained that, during the aforementioned period, the DREMEH formalized a total of 200 natural and/or legal subjects, which corresponds to 2.16% of small-scale miners who have formal exploitation and/or benefit activities. Therefore, once the respective evaluation was carried out, it was possible to discover limited and ineffective progress in the mining formalization process, as well as the barriers that miners face in achieving formalization.